On the use of the Lotus Blossom Technique to Foster Collaboration among Students in Software Development - Kleinpaul, Enzo; Pires, Alexandre; Machado, Letícia; Parizi, Rafael (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2025: Anais do XX Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2025.6892, 2025)
Collaboration is essential in software development but is often hindered by skill gaps and communication barriers. Techniques like Lotus Blossom provide a structured brainstorming approach to enhance teamwork and ideation. However, its role in fostering collaboration in product discovery remains underexplored. This study examines how undergraduate students applied the Lotus Blossom technique to enhance collaboration. As a methodology, we conducted a 2.5-hour activity where students applied the technique. Researchers assessed its impact using questionnaires. Our findings indicate that Lotus Blossom improved collaboration, helping students structure ideas, coordinate problem-solving, and strengthen teamwork. As a contribution, this study validates the Lotus Blossom technique as an effective method for fostering collaboration in software development education.